Implementasi AT89C51 pada Perancangan Sistem Penguncian Pintu Otomatis - Satriawaty Mallu; Fauzi Oswisa Putra (PROGRESS, 2020)
Opening or accessing a room using human power can be some troublesome things such as losing the key, having to find a double lock or repairing the lock, holding the door handle, pushing the door and locking the door back. Gate locking that directly uses a PIN or password is needed for the security and privacy of a special room. The implementation of the AT89C51 Microcontroller on a tool designed is aimed at a special or privacy room such as a bank vault. The purpose of this research is how to realize the system of opening and closing doors that can move directly by entering a combination of numbers. Another purpose of the system is made to facilitate mobility, so that for busy people can be avoided from the business of opening doors manually that can be time-consuming for those who have busy. The results of this study will be published in the Progress Journal of the final semester of 2019/2020 published by P3M STMIK Profesional Makassar.